Nitrogen–use efficiency in different vegetation type at Cikaniki Research Station, Halimun-Salak Mountain National Park, West Java (Biodiversitas Journal of Biological Diversity, 2016)
A research about nitrogen–use efficiency (NUE) and trees identification was conducted at different vegetation type at Cikaniki, Halimun- Salak National Park, West Java. Plot quadrate methods (20 x 50 m) was used to analyze trees vegetation and Kjeldahl methods was used to analyze leaf nitrogen. The width and length of the leaf was also measured to obtain the leaf surface area. The result showed that there are 61 individual trees which consisted of 24 species was identified. The species which have 5 highest important value are Altingia excelsa (64,657), Castanopsis javanica (39,698), Platea latifolia (27,684), Garcinia rostrata (21,151), and Schima walichii (16,049). FuthermoreEugenia lineata (13,967), Melanochyla caesa (12,241), Quercus lineata (10,766), platea excelsa (10,766) have lower important value. Other trees have important value less than 10. Morphological and nitrogen content analyze were done on 4 species : Quercus lineata, G. rostrata, A. excelsa, and E. lineata. Among them, Quercus lineata has highest specific leaf area (SLA) (0,01153), followed by G. rostrata (0,00821), A. excelsa (0,00579), and E. lineata (0,00984 g/cm2. The highest number of stomata was found on A. excelsa (85,10/mm2), followed by E. lineata (74,40/mm2), Q. lineata (53,70/mm2), and G. rostrata (18,4 /mm2). The emergent species (A. excelsa and Q. lineata)have higher nitrogen content than the underlayer species (G. rostrata and E. lineata). A. excelsa have highest nitrogen use efficiency (28,19%) compare to E. lineata (23,81%) , Q. lineata (19,09%), and G. rostrata (14,87%). Although not significant, emergen species have higher NUE than underlayer species.© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: nitrogen-use efficiency, vegetation type, plants, West Java